A vision of the defeated: The sense of history, according to peasant traditions of Paucartambo (Cusco-Peru) - Delran Cousy, Guido Gerardo (1974)
The province of Paucartambo is located to the East of the department of Cusco, in the last Andean foothills that dominate the jungle extensions. To date, the haciendas control the peasant population grouped in communities. We are in the presence of a rural society whose archaic structures are maintained by the domination of those "broker of influence" who are the mistis of the provincial capital.